Health care waste management and sustainable development goals in Malaysia - Mohd Tohit, Nor Faiza; Hassan, Noor Artika; Yusof, Muhammad Zubir (Zibeline Internatioal, 2019)
This review paper focuses on the definition of health care waste and its management in Malaysia. This review paper also sheds the light on the legislation related to hazardous waste in Malaysia. Subsequently, it explores the relation of healthcare waste with the Sustainable Development Goals (SDGs) outlined by United Nation.